Pengaruh Faktor Sikap, Gaya Hidup, Budaya, Kelompok Acuan, Media Terhadap Keputusan Pembelian Konsumen Cokelat Premium Di Won.dis Cokelat - Deliana Putri Hapsari; Nanik Dara Senjawati; Heni Handri Utami (Agrisociabus, 2023)
UMKM Won.dis Cokelat has a wide range of processed chocolate products with a variety of flavors making the majority of consumers Won.dis Cokelat prefer to buy the highest selling or best-selling products. The premium chocolate variant is a product with little sales. By looking at the small sales, companies need to pay attention to what factors influence consumers' decisions in making purchases of Premium Chocolate products. The purpose of this research was to determine the factors that influence consumers in making purchase decisions on Premium Chocolate products. The method used is a quantitative research method with a case study approach. The sampling method used a nonprobability sampling method with accidental sampling technique. The number of samples used in this study was 100 respondents. The data sources used are primary data and secondary data. Data collection techniques use interviews and questionnaires. The analytical techniques used are descriptive analysis and logistic regression analysis. The Result showed that: 1) variables of attitude, lifestyle, culture, reference groups and media influence together on the purchase decision of Premium Chocolate products at UMKM Won.dis Cokelat. 2) variables of attitude, lifestyle and media partially affect the purchasing decision of Premium Chocolate products at UMKM Won.dis Cokelat.